Potential effects of minimum unit pricing at local authority level on alcohol-attributed harms in North West and North East England: a modelling study - Alan Brennan; Colin Angus; Robert Pryce; Penny Buykx; Madeleine Henney; Duncan Gillespie; John Holmes; Petra S Meier (NIHR Journals Library, 2021)
Background: In 2018, Scotland implemented a 50p-per-unit minimum unit price for alcohol. Previous modelling estimated the impact of minimum unit pricing for England, Scotland, Wales and Northern Ireland. Decision-makers want to know the potential effects of minimum unit pricing for local authorities in England; the premise of this study is that estimated effects of minimum unit pricing would vary by locality. Objective: The objective was to estimate the potential effects on mortality, hospitalisations and crime of the implementation of minimum unit pricing for alcohol at local authority level in England. Design: This was an evidence synthesis, and used computer modelling using the Sheffield Alcohol Policy Model (local authority version 4.0). This study gathered evidence on local consumption of alcohol from the Health Survey for England, and gathered data on local prices paid from the Living Costs and Food Survey and from market research companies' actual sales data. These data were linked with local harms in terms of both alcohol-attributable mortality (from the Office for National Statistics) and alcohol-attributable hospitalisations (from Hospital Episode Statistics) for 45 conditions defined by the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision. These data were examined for eight age-sex groups split by five Index of Multiple Deprivation quintiles. Alcohol-attributable crime data (Office for National Statistics police-recorded crimes and uplifts for unrecorded offences) were also analysed. Setting: This study was set in 23 upper-tier local authorities in North West England, 12 upper-tier local authorities in the North East region and nine government office regions, and a national summary was conducted. Participants: The participants were the population of England aged ≥ 18 years. Intervention: The intervention was setting a local minimum unit price. The base case is 50p per unit of alcohol. Sensitivity analyses were undertaken using minimum unit prices of 30p, 40p, 60p and 70p per unit of alcohol. Main outcome measures: The main outcome measures were changes in alcohol-attributable deaths, hospitalisations and crime. Savings in NHS costs, changes in alcohol purchasing and consumption, changes in revenue to off-trade and on-trade retailers and changes in the slope index of inequality between most and least deprived areas were also examined. Results: The modelling has proved feasible at the upper-tier local authority level. The resulting estimates suggest that minimum unit pricing for alcohol at local authority level could be effective in reducing alcohol-attributable deaths, hospitalisations, NHS costs and crime. A 50p minimum unit price for alcohol at local authority level is estimated to reduce annual alcohol-related deaths in the North West region by 205, hospitalisations by 5956 (-5.5%) and crimes by 8528 (-2.5%). These estimated reductions are mostly due to the 5% of people drinking at high-risk levels (e.g. men drinking > 25 pints of beer or five bottles of wine per week, women drinking > 17 pints of beer or 3.5 bottles of wine per week, and who spend around £2500 per year currently on alcohol). Model estimates of impact are bigger in the North West and North East regions than nationally because, currently, more cheap alcohol is consumed in these regions and because there are more alcohol-related deaths and hospitalisations in these areas. A 30p minimum unit price has estimated effects that are ≈ 90% lower than those of a 50p minimum unit price, and a 40p minimum unit price has estimated effects that are ≈ 50% lower. Health inequalities are estimated to reduce with greater health gains in the deprived areas, where more cheap alcohol is purchased and where there are higher baseline harms. Limitations: The approach requires synthesis of evidence from multiple sources on alcohol consumption; prices paid; and incidence of diseases, mortality and crime. Price elasticities used are from previous UK analysis of price responsiveness rather than specific to local areas. The study has not estimated 'cross-border effects', namely travelling to shops outside the region. Conclusions: The modelling estimates suggest that minimum unit pricing for alcohol at local authority level would be an effective and well-targeted policy, reducing inequalities. Future work: The Sheffield Alcohol Policy Model for Local Authorities framework could be further utilised to examine the local impact of national policies (e.g. tax changes) or local policies (e.g. licensing or identification and brief advice). As evidence emerges from the Scottish minimum unit price implementation, this will further inform estimates of impact in English localities. The methods used to estimate drinking and purchasing patterns in each local authority could also be used for other topics involving unhealthy products affecting public health, for example to estimate local smoking or high-fat, high-salt food consumption patterns. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 9, No. 4. See the NIHR Journals Library website for further project information.